Mediastinal hemangioma: Masquerading as pleural effusion - J Deepak (Journal of Indian Association of Pediatric Surgeons, 2013)
We present a rare case of mediastinal hemangioma in a 4-year-old child. The child presented with cough and fever and the chest radiograph revealed right pleural effusion. On further work-up with chest computed tomography mediastinal cystic mass occupying the right hemithorax was identified. The cystic mass was resected completely through a right thoracotomy. Histopathological examination established the final diagnosis of mediastinal capillary hemangioma.